PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Julita Pinondang Tamba; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2021)
This study aims to determine the effects of corporate governance mechanism on the financial performance of manufacturing companies. Financial performance is proxied by Cash Flow Return On Assets (CFROA) as a measure of financial performance based on the company's operations. The corporate governance mechanism is determined by the variables of board of commissioners, board of directors, institutional ownership, and managerial ownership.This research used manufacturing companies during the 2017-2019 with total sample is 146 samples. Sampling based on purposive sampling method that follows certain criteria(s). Multiple regression analysis is the analysis method used in this research. The results of this study indicates that effectiveness of Board of Directors and Institutional Ownership have a positive significant effect on CFROA. Beside that, Board of Commisioners and Managerial Ownership have positive and insignificant on CFROA.